2019
DOI: 10.1096/fasebj.2019.33.1_supplement.666.5
|View full text |Cite
|
Sign up to set email alerts
|

The opioid receptor positive allosteric modulator BMS‐986187 enhances some, but not all, delta‐opioid receptor mediated behaviors

Abstract: Activation of the delta opioid receptor (DOR) by orthosteric agonists produces antinociception, antihyperalgesia, antidepressant‐like effects, and convulsions in animal models. Positive allosteric modulators (PAMs) bind to a receptor site distinct from the orthosteric binding site and can augment the activity of the endogenous system. Therefore, a DOR PAM could be an effective strategy for eliciting potential therapeutic effects without convulsions. To evaluate this hypothesis, we investigated the ability of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…DOR knockout mice (oprd1 deficient) exhibit anxiety and depressive-like behaviours (48), and selective DOR agonists have anxiolytic and anti-depressant effects in mice (49). It has been reported that BMS-986187 has anti-depressant like effects in mice that were blocked by naltrindole and absent in DOR knockout mice (29,50). Depression and functional GI disorders are comorbidities with reported 30% coincidence (51), therefore there is potential for DOR PAMs to treat both the central and peripheral mediators of IBS symptoms.…”
Section: Clinical Relevancementioning
confidence: 99%
“…DOR knockout mice (oprd1 deficient) exhibit anxiety and depressive-like behaviours (48), and selective DOR agonists have anxiolytic and anti-depressant effects in mice (49). It has been reported that BMS-986187 has anti-depressant like effects in mice that were blocked by naltrindole and absent in DOR knockout mice (29,50). Depression and functional GI disorders are comorbidities with reported 30% coincidence (51), therefore there is potential for DOR PAMs to treat both the central and peripheral mediators of IBS symptoms.…”
Section: Clinical Relevancementioning
confidence: 99%